Allergic sensitization pattern of patients in Brazil - Carolina Sanchez Aranda; Renata R. Cocco; Felipe F. Pierotti; Emanuel Sarinho; Flávio Sano; Arnaldo Porto; Nelson Rosário; Herberto J. Chong Neto; Ekaterini Goudouris; Lillian S. Moraes; Neusa F. Wandalsen; Marcia C. Mallozi; et al. (Elsevier, 2021)
Objective: Allergic sensitization is one of the key components for the development of allergies. Polysensitization seems to be related to the persistence and severity of allergic diseases. Furthermore, allergic sensitization has a predictive role in the development of allergies. The aim of this study was to characterize the pattern of sensitization of atopic patients treated at different pediatric allergy referral centers in Brazil. Methods: A nation-wide transversal multicenter study collected data on patients attended in Brazil. Peripheral blood samples were collected to determine the serum levels of allergen-specific IgE. If allergen-specific IgE was higher than 0.1 kUA/L, the following specific components were quantified. Results: A total of 470 individuals were enrolled in the study. Mite sensitization was the most frequent kind in all participants. A high frequency of sensitization to furry animals and grasses featured in the respiratory allergies. Regarding components, there was a predominance of sensitization to Der p 1 and Der p 2. It has been verified that having a food allergy, atopic dermatitis, or multimorbidity are risk factors for the development of more severe allergic disease. Conclusion: Studies on the pattern of allergic sensitization to a specific population offer tools for the more effectual prevention, diagnosis, and treatment of allergic diseases. Sensitization to dust mites house was the most prevalent in the evaluated sample. High rates of sensitization to furry animals also stand out. Patients with food allergy, atopic dermatitis, or multimorbidity appear to be at greater risk for developing more severe allergic diseases.